Gifts, Markets and Economies of Desire in Virginia Woolf - Simpson, K. author. aut Link
IX, 200 p.
Keywords: This book brings a new dimension to the critical debate about the complex relationship of Woolf to the marketplace and commodity culture through a focus on the gift economy at work in Woolf's writing, exploring the political subversiveness of the gift and its significance in her modernist aesthetics.